1999
DOI: 10.1177/00912709922007949
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Lamotrigine Adjunctive Therapy in Adults with Epilepsy

Abstract: Plasma concentrations of lamotrigine, an antiepileptic drug obtained in three adult controlled clinical trials conducted in the United States were pooled and analyzed using NONMEM, a population pharmacokinetic computer program, to facilitate development of dosing guidelines. A total of 2,407 lamotrigine plasma concentrations from 527 patients with epilepsy were analyzed. Regression equations for oral clearance were developed as a function of body size, age (18-64 years), gender, race, and use of concomitant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
53
2
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 21 publications
12
53
2
3
Order By: Relevance
“…The induction effect of PB or CBZ was observed; thus, CL was increased by 1.9-2.4 fold compared to monotherapy. These results are similar to those from previous studies conducted in patients taking these drugs that also reported increased LTG CL with values ranging from 0.044 to 0.084 L·h -1 ·kg -1 [7,[25][26][27] .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The induction effect of PB or CBZ was observed; thus, CL was increased by 1.9-2.4 fold compared to monotherapy. These results are similar to those from previous studies conducted in patients taking these drugs that also reported increased LTG CL with values ranging from 0.044 to 0.084 L·h -1 ·kg -1 [7,[25][26][27] .…”
Section: Discussionsupporting
confidence: 91%
“…This unexplained variability was of similar magnitude to those reported in earlier studies [7,[13][14][15][16][32][33][34] .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations